1951
DOI: 10.1152/ajplegacy.1951.165.2.466
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of the ACTH Regulating Effect of Corticoids

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1954
1954
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This observation has been confirmed by many investigators (2-7), but not by all (8). In man the clinical, morphological and biochemical evidence for steroidal inhibition of pituitary secretion is impressive but there are few actual measurements of blood ACTH reported.…”
mentioning
confidence: 71%
“…This observation has been confirmed by many investigators (2-7), but not by all (8). In man the clinical, morphological and biochemical evidence for steroidal inhibition of pituitary secretion is impressive but there are few actual measurements of blood ACTH reported.…”
mentioning
confidence: 71%
“…The findings of Sayers & Sayers (1947) have been only partially confirmed. Some workers have found that the stress-induced secretion of ACTH can be prevented only by massive doses of corticoids (Hodges, 1953(Hodges, , 1954Abelson & Baron, 1952) and others have failed to show any ability of these steroids to suppress ACTH release (Moya & Selye, 1948;Hall, Finerty, Hall & Hess, 1951;Fortier, Yrarrazaval & Selye, 1951). A further demonstration that the secretion of ACTH -is not necessarily controlled by changes in the level of corticoids in the blood was provided by Sydnor & Sayers (1954) when they found that adrenalectomized animals are still capable of secreting adrenocorticotrophic hormone in response to stress.…”
Section: (Received 5 October 1959)mentioning
confidence: 99%
“…The reduction in size of the " X " zone in these experiments could be due to stimulation of the zona fasciculata to produce corticosteroids (or their intermediates), some of which have androgenic activity (Moon, 1961). Such adrenal gland stimulation could be effected by the small amounts of histamine absorbed from the nasal mucosa, mouth, or digestive tract and act in a similar manner to the " stress" reaction (Fortier, Yrarrazaval and Selye, 1951;Ohno, 1962). Involution of the " X " zone appeared less acute than that observed in stressed, starved or formalin-injected mice (Ohno, 1962) but some lipid accumulation, cedema and increased vascularity were noted.…”
Section: Discussionmentioning
confidence: 99%